The poem introduction in Al-Mutanabbi’s Poetry - Al-Hasan , Hassan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Al-Mutanabbi, as we all know, is a poet who filled the world with poetry providing a tale and reflecting the sublimity of creation and art.He is still like a torrential spring from which scholars drinkn to quench the thierdt of their pens in search of his creative works, trying to reveal the secret of that creation which involves inventive psychological feelings that made him form his poetry with wonderful aesthetic artistry, something which, gave Arabic a particular dealing with the word use which, perhaps, is almost unique to Al-Mutanabbi so that this creation which remained constanly with him till he became famous for it as if it had been his identification card he held. No sooner does ascholar read that language than he sees Al-Mutanabbi’s ID Card which has later became the ID card of Arabic poetry, affecting its advance and restrationcreativey, aristically and intellectually throughout ages and history.